THE SOCIO-PEDAGOGICAL NECESSITY OF PREPARING FUTURE PEDAGOGUES FOR PROFESSIONAL ACTIVITY (Scientific journal of the Fergana State University, 2025)
In the article, the theoretical-methodological foundations of the development of accountability skills in the professional activity of future pedagogues, the system of development of accountability skills in preparing future pedagogues for professional activity based on independent education, in the preparation of future pedagogues for professional activity based on independent education The effectiveness of developing accountability skills has been studied. Pedagogical bases and priorities for developing accountability skills in preparing future pedagogues for professional activities were also analyzed.